Exploratory Analysis of Treading Water Coordination and the Influence of Task and Environmental Constraints - Button, Chris; Brouwer, Luka; Schnitzler, Christophe; de Poel, Harjo J. (Frontiers in Psychology, 2019)
The radical embodied cognition approach to behavior requires emphasis upon how humans adapt their motor skills in response to changes in constraint. The aim of this exploratory study was to identify how the typical coordination patterns used to tread water were influenced by constraints representative of open water environments. Twenty-three participants were measured while treading water (TW) in a swimming flume in four conditions: a) in still water, wearing a bathing suit (baseline); b) wearing typical outdoor clothing (clothed); c) with an additional cognitive task imposed (dual task), and; d) against a changing current (flow). Mixed methods kinematic analysis revealed four different TW coordination patterns were used across the conditions. The four TW patterns used represent a hierarchy of expertise in terms of the capacity to generate continuous lift forces, where pattern 1 (the lowest skill level) involving predominantly pushing and kicking limb movements (N=1); pattern 2, was a movement pattern consisting of legs pushing/kicking and arms sculling (N=7); pattern 3 was synchronous sculling of all four limbs (N=6); and pattern 4 was the ‘eggbeater kick’ (the highest skill level), with asynchronous sculling movements of the legs (N=9). The four TW patterns were generally robust to the modified constraints. The higher skilled patterns (i.e., patterns 3 and 4) appeared to be the most stable coordination patterns. These results suggest that learning to perform more complex patterns to tread water might be an asset to survive in life-threatening situations.